Tradisi Nastamir Sebagai Implementasi Metode Jibril dalam Pembelajaran Al Qur'an di Pondok Tremas - Ilham Majid (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
This research aims to determine the role of implementing the Jibril Method in developing the Al-Qur'an reading skills of students at the Pondok Tremas Pacitan Islamic College in the tradition of Nastamir activities. The object of this research is the implementation of the Jibril Method, the history and practice of the Nastamir tradition. This research approach is to use descriptive qualitative research, by conducting field studies through: observation, interviews and documentation. The research results in this article explain the internal and external problems of female students in studying the Qur'an in Islamic boarding schools as well as the role of Nastamir activity traditions as a means of training female students to be diligent and disciplined. By adopting the Jibril method as the main indicator to support students' learning achievement in studying the Koran. The existence of the Nastamir tradition is still maintained and continues from time to time at the Islamic College Pondok Tremas Pacitan.